Government Policies and Sustainable Food Systems: Navigating Challenges, Seizing Opportunities, and Advancing Environmental and Social Resilience - Agarwala, Carthy; Jemaneh, Jemaneh; Kassie, Youngs (Law and Economics, 2022)
This research delves into the intricate landscape of government policies shaping sustainable food systems, with a focus on addressing food security challenges and fostering environmental, economic, and social sustainability. Through a comprehensive analysis of global and regional contexts, the study elucidates the multifaceted challenges governments face, ranging from climate variability and globalization pressures to social inequities and policy implementation gaps. However, amidst these challenges, the research identifies compelling opportunities for improvement and innovation. Technological advancements, such as precision agriculture and biotechnological innovations, emerge as transformative tools for enhancing agricultural practices and environmental resilience. Climate-smart agriculture, sustainable supply chains, and policy coherence represent pathways toward reconfiguring global trade dynamics and building more resilient food systems. The research also underscores the crucial role of education, capacity building, and international collaboration in fostering sustainable practices. It advocates for whole-of-government approaches, incentive structures, and public awareness campaigns to drive transformative change in both production and consumption patterns. The findings of this research carry significant implications for policy development, emphasizing the need for integrated, adaptive, and collaborative approaches. The abstract encapsulates the essence of a call to action-a call for governments, researchers, and stakeholders to collectively shape a future where sustainable, equitable, and resilient food systems nourish communities and safeguard the health of the planet